CEO Power dan Penghindaran Pajak pada Perusahaan Pertambangan di Indonesia - Diastuti, Evita Marcella; Adiati, Arum Kusumaningdyah (Jurnal Akuntansi dan Bisnis, 2024)
This study aims to examine the relationship between CEO power and tax avoidance in mining companies listed on the Indonesia Stock Exchange (IDX) from 2018 to 2022. The research population consists of mining sector companies listed on the IDX during the 2018-2022 period, using purposive sampling as the sample selection method. Sixty-four mining sector companies over five years were selected as the research sample. The data analysis technique employed in this study is panel data analysis. The results of the analysis show that CEO power has a negative effect on tax avoidance, indicating that the more powerful the CEO, the less likely the company is to engage in tax avoidance practices. Firm size and inventory intensity do not affect tax avoidance, whereas profitability and leverage have positive and negative effects on tax avoidance, respectively. This study contributes to the literature on the factors influencing tax avoidance.